2005
DOI: 10.1557/proc-878-y3.3
|View full text |Cite
|
Sign up to set email alerts
|

Ammonothermal Crystallization of AlN Crystals

Abstract: III-Nitrides (GaN, AlN and other compounds) have attracted vast interest due to their unique properties and potential applications in optoelectronic devices operating in the blue and UV spectral regions and for the construction of electronic devices capable of operating under high power and high temperature conditions. Nanocrystalline AlN powder were obtained by AMMONO method, in which nitridization of Al metal occurs in highly chemical active supercritical ammonia using both NH 4 Cl as mineralizer. The experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
0
0
Order By: Relevance
“…In the acidic system, Y. C. Lan et al [159] produced their powder at 450 °C with an NH4Cl mineralizer. A. I. Motchanyy et al [223] reported that the nucleation results below 450 °C were the worst with the NH4Cl mineralizer. Correspondingly, 450 °C is the lowest temperature at which noticeable nucleation of AlN has been observed in the acidic environment.…”
Section: Crystallization Results Will Be Discussed In the Followingmentioning
confidence: 99%
“…In the acidic system, Y. C. Lan et al [159] produced their powder at 450 °C with an NH4Cl mineralizer. A. I. Motchanyy et al [223] reported that the nucleation results below 450 °C were the worst with the NH4Cl mineralizer. Correspondingly, 450 °C is the lowest temperature at which noticeable nucleation of AlN has been observed in the acidic environment.…”
Section: Crystallization Results Will Be Discussed In the Followingmentioning
confidence: 99%